Inclusive participation as a way to good educational governance and quality education - Spajić-Vrkaš, Vedrana (2012)
Good educational governance and quality education have always been dealt with as interrelated and interdependent concepts. In the same time, the meaning of both concepts is highly contested. What constitutes good governance and quality in education has been constantly redefined as the consequence of the revision of the purpose of education when social, cultural and political contexts change. In a contemporary democracy, for which the protection of human rights, equality and the rule of law is essential, the quest for good educational governance and quality education means primarily wider involvement and more openness in the process of decision-making. This can be reached through deliberation, i.e. through active participation, dialogue and exchange of perspectives held by all educational stakeholders. An inclusive participation leads to a consensual decision on all important aspects of education in the context of often conflicting interests. Such practice is particularly important when main educational stakeholders – teachers, students and parents - are concerned. Their participation is formative and instrumental. In the one hand, it improves their decision-making competences, their sense of efficacy and ownership in learning and teaching, and their trust in the value of education which, in the other hand, improves accountability and effectiveness of educational institutions. Finally, inclusive participation of teachers, students and parents contributes to developing not only school as a democratic community of knowledge but of students as active and responsible citizens. Drawing from this, the presentation will be focused on the following six broad issues: a) how are good educational governance, quality education, participation and democracy linked together ; b) what does participation, in general, and all-inclusive or integrative participation, in particular, means in the context of contemporary educational changes which aim at enhancing the wellbeing of the individual and the society by strengthening democracy and knowledge-based economy ; c) how does the inclusive model of participation, with teachers, students and parents as the main stakeholders, contribute to good educational governance and quality education ; d) what types of arguments support their participation in educational decision-making ; e) when the inclusive model of participation may fail to produce the expected results ; and f) what are the precondition for the inclusive model of participation to be successful.
ENG